2017
DOI: 10.1055/s-0037-1603956
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Incision Negative-Pressure Therapy in Obese Patients Undergoing Cesarean Delivery: A Randomized Controlled Trial

Abstract: Background  Postcesarean wound morbidity is a costly complication of cesarean delivery for which preventative strategies remain understudied. Objective  We compared surgical site occurrences (SSOs) in cesarean patients receiving closed-incision negative-pressure therapy (ciNPT) or standard-of-care (SOC) dressing. Study Design  A single-center randomized controlled trial compared ciNPT (5–7 days) to SOC dressing (1–2 days) in obese women (body mass index [BMI] ≥ 35), undergoing cesarean delivery between 2012 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 17 publications
2
71
1
Order By: Relevance
“…The reduction in overall complications and hospital stay are directly related to each other and both have been reported before. 13,15,17,18,27 Our results vary from some earlier reports 14,15,20 where a reduction in the number of complications requiring surgery was reported. Our study did not find this during the initial stay in hospital, but we found a reduction in open wounds at 3 months after surgery, which indirectly resulted in a reduction for the need of later surgical revisions.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The reduction in overall complications and hospital stay are directly related to each other and both have been reported before. 13,15,17,18,27 Our results vary from some earlier reports 14,15,20 where a reduction in the number of complications requiring surgery was reported. Our study did not find this during the initial stay in hospital, but we found a reduction in open wounds at 3 months after surgery, which indirectly resulted in a reduction for the need of later surgical revisions.…”
Section: Discussioncontrasting
confidence: 99%
“…Negative pressure treatment resulted in several positive outcomes, such as decrease in overall complications, significantly reduced length of stay in hospital, and decrease in the number of open recurrent wounds at 3 months after discharge from hospital, which are all important outcome measures. The reduction in overall complications and hospital stay are directly related to each other and both have been reported before . Our results vary from some earlier reports where a reduction in the number of complications requiring surgery was reported.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The successful application of ciNPT on clean, closed wounds has been reported in a broad spectrum of patients and operative interventions resulting in positive clinical results in a majority of the RCTs identified in the literature search ( Table 2) [11][12][13][14][15][16][17][18][19]. Similarly, rates of SSIs, surgical site complications, readmissions, and/or reoperations were reduced in patients receiving ciNPT compared to historical control populations [20][21][22][23][24][25].…”
Section: Literature Searchmentioning
confidence: 95%
“…A total of 35 articles discussed prophylactic VSD (pVSD) for abdominal incisions with primary suture, of which 6 were RCTs 32 , 33 , 34 , 35 , 36 , 37 and 29 were observational studies. 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 …”
Section: Recommendationsmentioning
confidence: 99%